PENGARUH KARAKTERISTIK PEKERJAAN, PELATIHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA DOSEN MELALUI KOMITMEN ORGANISASI PADA UNIVERSITAS MARITIM RAJA ALI HAJI PROVINSI KEPULAUAN RIAU - Yanti, Mira Dama; Marnis, Marnis; Widayatsari, Any (Komunitas Manajemen Kompetitif, 2025)
This study aims to determine and analyze the effect of job characteristics, training and organizational culture on lecturer performance through organizational commitment at Raja Ali Haji Maritime University, Riau Archipelago Province. This study uses a quantitative approach. The population in this study were 131 UMRAH lecturers. The sampling method used was proportional stratified random sampling, the total number of samples used was 131 people. The data used in this study are primary and secondary data, while the data collection technique uses a questionnaire. The data analysis technique used in this study is Path Analysis, using the SPSS analysis tool. The results of the study stated that Job Characteristics had a direct and significant positive effect on Lecturer performance, training had a direct on Lecturer performance, organizational culture had a significant positive effect on Lecturer performance and organizational commitment had a significant positive effect on Lecturer performance. While indirectly Job Characteristics has a significant positive effect on Lecturer performance through commitment as an intervening variable, training has a direct on Lecturer performance through commitment as an intervening variable, organizational culture has a significant positive effect on Lecturer performance through commitment as an intervening variable. Organizational commitment is a much-needed variable because it can mediate the effect of job characteristics, Training and organizational culture on lecturer performance, but organizational commitment is not the only variable that can mediate the effect of training on lecturer performance. Keywords: Job Characteristics; Training; Organizational Culture; Organizational Commitment and Employee Performance